Cathode material capable of spontaneously forming spinel type lithium-rich metal oxide as well as preparation method and application of cathode material

The transition metal oxide MO exposed to a specific crystal surface was prepared by electrospinning method and used for the positive electrode material of lithium oxygen battery, which solved the problems of Li2O2 generation and difficulty in decomposition, and achieved high energy efficiency and cycle stability of lithium oxygen battery.

CN119890336AInactive Publication Date: 2025-04-25DALIAN MEINIU NEW ENERGY CO LTD

Patent Information

Application Number
CN202510381585.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The poor conductivity of Li2O2 generated in lithium oxygen batteries and its difficult decomposition problems lead to a decrease in high charging voltage and energy efficiency, and poor cycle stability.

Method used

The transition metal oxide MO exposing a specific crystal surface is prepared by electrospinning method, such as manganese oxide MnO, as the positive electrode material of lithium oxygen batteries, and spinel-type lithium-rich metal oxides are spontaneously formed to avoid the formation of Li2O2 and promote its decomposition at low potential.

Benefits of technology

It realizes extremely low voltage (about 3.2V) and high energy efficiency (82.18%) of lithium oxygen batteries when charging, while ensuring the cyclic stability of the reaction, avoiding the occurrence of side reactions, and reducing commercial costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890336A_ABST
    Figure CN119890336A_ABST
Patent Text Reader

Abstract

The invention discloses a cathode material capable of spontaneously forming a spinel type lithium-rich metal oxide as well as a preparation method and application of the cathode material, and relates to the technical field of Li-O2 batteries. The cathode material for spontaneously forming the spinel type lithium-rich metal oxide is a transition metal oxide MO which is prepared by an electrostatic spinning method and exposes a specific crystal face; wherein M is Mn, Co, Ni or Fe. Aiming at the problems that Li2O2 with poor conductivity is generated in the current lithium-oxygen battery and the Li2O2 is difficult to decompose, the invention provides a cheap transition metal oxide MO which can avoid the formation of Li2O2 and promote the decomposition of Li2O2 at low potential and exposes a specific crystal face, and when the transition metal oxide MO is applied to the lithium-oxygen battery, the cycling stability and the energy efficiency can be enhanced, and the lithium-oxygen battery has a good application prospect. The electrochemical performance of the lithium-oxygen battery can be improved, the commercial cost can be reduced, and the material is more expected to become a key material for replacing noble metal in the positive electrode of the lithium-oxygen battery in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of Li-O2 batteries in metal-air batteries, and in particular to a cathode material that spontaneously forms a spinel-type lithium-rich metal oxide, and a preparation method and application thereof. Background Art

[0002] Lithium-oxygen batteries have extremely high theoretical energy density and are extremely lightweight, and are considered to be the most promising new generation of energy storage devices. During the discharge process of lithium-oxygen batteries, the battery will undergo an oxygen reduction (ORR) reaction to generate lithium peroxide (Li2O2). During the charging process, as the charging voltage gradually increases, Li2O2 will gradually decompose into Li and O2, which is the oxygen evolution reaction (OER). However, the Li2O2 produced during the discharge process is a solid with poor conductivity and is difficult to decompose. The high charging voltage caused by it not only causes a decrease in energy efficiency, but also easily causes excessive side reactions, which seriously deteriorates its subsequent cycles. Therefore, it is particularly important to promote its decomposition or avoid its generation through suitable catalysts to improve energy efficiency and cycle reversibility.

[0003] Li2O2 is easy to generate because O2 - The existence of it is easy to + Rapid contact to form the intermediate lithium superoxide (LiO2 - ), and then form Li2O2. The reason why Li2O2 has poor conductivity and is difficult to decompose is that there is a wide band gap between its conduction band and valence band. The current common solution is to apply precious metals, transition metals and their oxides to the cathode of lithium oxygen batteries to improve the energy efficiency and cycle stability of the battery. The problem is that precious metals can avoid the formation of Li2O2 through appropriate adsorption (desorption) energy, and are more likely to show excellent performance and cycle stability, but the resources of precious metals are limited, which also increases the cost; using cheap transition metal salts or their complexes through a classic heat treatment process to form metals or metal oxides with special morphology or special structure, through its faster kinetic characteristics and excellent ORR catalytic activity to change the formation path or appearance structure of Li2O2, although it can improve the problem of excessively high charging voltage, however, this only focuses on studying the changes in the reaction rate caused by their corresponding processes when Li2O2 is formed or decomposed, and cannot substantially avoid the formation of Li2O2 and improve battery performance. Therefore, it is impossible to effectively solve the problem of high charging voltage. Summary of the invention

[0004] In view of the problem of poor conductivity of Li2O2 generated in current lithium-oxygen batteries and its difficulty in decomposition, one of the purposes of the present invention is to provide a cheap transition metal oxide MO with exposed specific crystal planes, which can avoid the formation of Li2O2 and promote its decomposition at low potential, enhance the cycle stability and improve the energy efficiency, not only improve the electrochemical performance of lithium-oxygen batteries, but also reduce commercial costs, and is expected to become a key material to replace precious metals in the positive electrode of lithium-oxygen batteries in the future.

[0005] To achieve the above-mentioned purpose of the invention, the technical solution adopted by the present invention is: a cathode material that spontaneously forms a spinel-type lithium-rich metal oxide, wherein the cathode material that spontaneously forms a spinel-type lithium-rich metal oxide is a transition metal oxide MO that exposes a specific crystal face prepared by an electrospinning method; wherein M=Mn, Co, Ni or Fe.

[0006] Furthermore, the cathode material of the spontaneously formed spinel lithium-rich metal oxide is manganese oxide MnO which is prepared by an electrospinning method and exposes a (111) specific crystal plane.

[0007] The second object of the present invention is to provide a method for preparing a cathode material that spontaneously forms a spinel-type lithium-rich metal oxide, comprising: Weighing manganese salt, cobalt salt, nickel salt or iron salt, polyvinyl pyrrolidone and cationic surfactant into a container, adding dimethylformamide to dissolve, sealing the container, stirring at room temperature for 10h-15h, and obtaining an electrospinning precursor solution; The electrospinning precursor solution is transferred into a syringe to prepare electrospinning fibers by an electrospinning method; The electrospun fiber is placed in a drying oven, dried at 50°C-70°C for 10h-15h, then heat treated in a N2 atmosphere, and then naturally cooled to room temperature to obtain a transition metal oxide MO with a specific crystal face exposed.

[0008] Furthermore, the manganese salt is selected from Mn(Ac)2, MnSO4 or Mn(NO3)2.

[0009] Furthermore, the cationic surfactant is cetyltrimethylammonium bromide (CTAB), and the added amount of cetyltrimethylammonium bromide is 75%-85% of the mass of the manganese element.

[0010] Furthermore, the conditions of the electrospinning method are: voltage 20kV-30kV, injection rate 0.5mL / h-1.0mL / h, and receiving distance 12cm-15cm.

[0011] Furthermore, the heat treatment is to increase the temperature to 750°C-850°C at a heating rate of 1°C / min-2°C / min and maintain the temperature for 2h-3h.

[0012] The third object of the present invention is to provide an application of a cathode material that spontaneously forms a spinel-type lithium-rich metal oxide, and to apply the above-mentioned transition metal oxide MO that exposes a specific crystal face as a positive electrode material to a lithium-oxygen battery.

[0013] Furthermore, the transition metal oxide MO and the conductive carbon material exposing the specific crystal plane are dissolved in a polyvinylidene fluoride N-methylpyrrolidone solution (PVDF / NMP solution) with a mass percentage concentration of 2%-7%, ultrasonicated for 30min-40min, and the obtained slurry is drop-coated on the carbon support to obtain the positive electrode material of the lithium oxygen battery.

[0014] Furthermore, the conductive carbon material includes carbon fiber, carbon nanotube, graphite or conductive carbon black Super P.

[0015] Compared with the prior art, the present invention has at least the following beneficial effects: The present invention mainly aims at the problem of low energy efficiency caused by the difficult-to-decompose Li2O2 in Li-O2 batteries. A transition metal oxide MO with exposed specific crystal faces is prepared by an electrospinning method and applied to the positive electrode material of Li-O2 batteries. During the discharge process, lithium-rich metal oxides are spontaneously formed, that is, by reacting with the intermediate LiO2 during the discharge process. - The reaction forms an intermediate product spinel lithium-rich metal oxide (LiM x O y ) (M = Mn, Co, Fe or Ni), which can avoid the high decomposition potential caused by the formation of Li2O2, and form transition metal oxides MO with different valence states after charging, which enables the lithium-oxygen battery to be charged at an extremely low voltage (about 3.2V) during charging, which not only enables the lithium-oxygen battery to show high energy efficiency (82.18%), but also continuously reacts with the intermediate LiO2 - The reaction can ensure the cycle stability of the reaction, which can not only improve its energy efficiency, but also avoid the occurrence of side reactions, making it possible to continue the charge and discharge process more stably. The resulting high energy efficiency is comparable to the performance of precious metals in Li-O2 batteries, which can replace the use of Pt and further reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 12 are SEM images of MnO prepared by the sol-gel method (A) and the electrospinning method (B) in Example 1.

[0018] Figure 2 TEM image (A) and the corresponding HRTEM image (with embedded SAED image) (B) of a single nanocube of MnO(111) prepared by electrospinning in Example 1.

[0019] Figure 3 is a SEM image of electrospun fibers prepared by different surfactants in Example 1; Among them, A: sodium dodecyl sulfate; B: hexadecyltrimethylammonium bromide; C: Tween 20.

[0020] Figure 4 These are the corresponding SEM images of the products before and after calcination with different concentrations of CTAB added in Example 1.

[0021] Figure 5 It is the corresponding XRD diagram of the product after calcination with different concentrations of CTAB in Example 1.

[0022] Figure 6 The deep discharge curves of the positive electrode material of Example 2, which is Super P (A, C) or MnO (111) + Super P (B, D), at different current densities and the SEM images after discharge at 500 mA / g.

[0023] Figure 7 This is the charge and discharge cycle curve of MnO (111) in Example 2 after it is applied to the lithium oxygen battery.

[0024] Figure 8 This is the XRD diagram of the positive electrode after discharge at a specific number of cycles in Example 2. DETAILED DESCRIPTION

[0025] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] According to a first aspect of an embodiment of the present invention, a cathode material that spontaneously forms a spinel-type lithium-rich metal oxide is provided. The cathode material that spontaneously forms a spinel-type lithium-rich metal oxide is a transition metal oxide MO that exposes a specific crystal plane and is prepared by an electrospinning method; wherein M=Mn, Co, Ni or Fe.

[0027] The transition metal oxide MO with exposed specific crystal faces provided by the present invention is applied to the positive electrode material of Li-O2 battery, and reacts with the intermediate LiO2 during the discharge process. - The reaction forms a spinel lithium-rich metal oxide (LiM x O y ), thereby avoiding the formation of Li2O2, allowing the lithium-oxygen battery to reduce the required voltage during the charging process, which can not only improve the energy efficiency of the lithium-oxygen battery, but also avoid the occurrence of side reactions and enable the lithium-oxygen battery to continue the charging and discharging process more stably.

[0028] In some feasible embodiments, the cathode material that spontaneously forms a spinel-type lithium-rich metal oxide is manganese oxide MnO that exposes a (111) specific crystal plane and is prepared by an electrospinning method.

[0029] In the present invention, when MnO with exposed (111) specific crystal face is used as the positive electrode of lithium oxygen battery, during the discharge process, the intermediate LiO2 - It is easy to contact with the (111) crystal plane of MnO and react to form lithium-rich manganese oxide (LiMnO4) instead of Li2O2, which can significantly reduce the voltage required for charging and greatly improve the energy efficiency of the battery. During charging, the intermediate product LiMnO4 will decompose to produce single lithium (Li) and manganese oxide (MnO x ), which will not cause serious polarization due to oxygen oxidation problems in subsequent cycles.

[0030] A second aspect of an embodiment of the present invention provides a method for preparing a cathode material that spontaneously forms a spinel-type lithium-rich metal oxide, comprising the following steps: 1) Preparation of electrospinning precursor solution: weigh manganese salt, cobalt salt, nickel salt or iron salt, polyvinyl pyrrolidone (PVP) and cationic surfactant in a container, add dimethylformamide (DMF) to dissolve, seal the container, stir at room temperature for 10h-15h to form a uniform solution, and obtain an electrospinning precursor solution; 2) transferring the electrospinning precursor solution into a syringe and preparing electrospinning fibers by an electrospinning method; 3) The electrospun fiber is placed in a drying oven and dried at 50°C-70°C for 10h-15h, then heat treated in a tubular atmosphere furnace under a N2 atmosphere, and naturally cooled to room temperature to obtain a transition metal oxide MO with a specific crystal face exposed.

[0031] The present invention is aimed at the positive electrode material of lithium oxygen battery. The special (111) crystal surface of transition metal is beneficial to the intermediate LiO2 -The stability of the material is particularly important. The present invention prepares a transition metal oxide MO exposing a specific (111) crystal face by adopting a special preparation method (electrospinning method). By improving the electrochemical properties of the positive electrode material, a significant reduction in the charging potential is achieved, thereby improving its cycle stability and energy efficiency performance. In the present invention, by adding a metal salt (Mn salt, Fe salt, Co salt or Ni salt) to the electrospinning precursor solution, uniformly loaded fibers can be obtained, and after further pyrolysis or carbonization, uniformly dispersed nanoparticles can be formed. The material prepared by the electrospinning method of the present invention is conducive to the uniform dispersion of metal ions. The transition metal oxide MO exposing the (111) crystal face is prepared by an electrospinning method combined with a heat treatment process. When applied to the cathode of a lithium-oxygen battery, the intermediate LiO2 - Stable and form lithium-rich metal oxide (LiM x O y ), avoids the generation of Li2O2 and reduces the voltage required for charging, greatly improving the energy efficiency of the battery, and is the only choice to replace precious metals in the future.

[0032] It should be noted that surfactants are divided into anionic surfactants, cationic surfactants and nonionic surfactants. In the present invention, when anionic surfactants are used, the corresponding fibers are not only entangled with each other, but also the continuity of the fibers is very poor. When nonionic surfactants are used, no obvious fiber structure is presented in the fibers. When cationic surfactants are used, the corresponding fiber structure is not only uniform in size distribution, but also there is no obvious agglomeration phenomenon between the fibers. Therefore, the preferred surfactant of the present invention is a cationic surfactant.

[0033] In some feasible embodiments, the manganese salt is selected from Mn(Ac)2, MnSO4 or Mn(NO3)2.

[0034] The present invention uses manganese salts such as Mn(Ac)2, MnSO4, Mn(NO3)2, etc., and performs spinning by an electrospinning method at room temperature. The results show that electrospun fibers can be successfully prepared without affecting the morphology of the electrospun fibers.

[0035] In some feasible embodiments, the cationic surfactant is cetyltrimethylammonium bromide (CTAB).

[0036] Specifically, after adding manganese salt to the spinning solution to form a uniform solution, the surfactant CTAB was added to not only 2+ It can be evenly dispersed on the surface of carbon nanofibers, and can reduce the surface tension of the solution, thereby reducing the voltage required during the electrospinning process and saving energy. In addition, during the calcination process, the evenly dispersed Mn 2+As the temperature rises, the metal oxide will gradually crystallize. The presence of CTAB can be adsorbed on the (111) crystal plane during the gradual crystallization process, and the generation rate of other crystal planes is suppressed, so that the metal oxide will continue to grow toward the (111) crystal plane, thereby exposing the (111) specific crystal plane. Therefore, the present invention preferably uses CTAB as the cationic surfactant. After using the surfactant CTAB, the (111) specific crystal plane can be fully exposed.

[0037] In some feasible implementations, the amount of cetyltrimethylammonium bromide added is 75%-85% of the mass of the manganese element.

[0038] Specifically, when the addition amount of CTAB is less than 75%, two problems will occur: first, it is not conducive to reducing the surface tension of the spinning solution and reducing the voltage required to be applied; second, it will reduce the regulatory effect on the growth of the MnO (111) crystal surface, resulting in enhanced disordered growth, which will cause defects and reduce the electrocatalytic performance. When the addition amount of CTAB is higher than 85%, CTAB, as a cationic surfactant, is easy to aggregate with each other when approaching the critical micelle concentration (CMC) and exists in the form of micelles, which will seriously affect the growth process of the crystal, causing the crystal surface exposure of the transition metal oxide to become unpredictable.

[0039] In some feasible embodiments, the conditions of the electrospinning method are: voltage 20 kV-30 kV, injection rate 0.5 mL / h-1.0 mL / h, and receiving distance 12 cm-15 cm.

[0040] The electrostatic spinning conditions proposed by the present invention can not only ensure the stability of the spinning process and the high quality of the fibers, but also improve the spinning efficiency.

[0041] In some feasible implementations, the heat treatment is to increase the temperature to 750°C-850°C at a heating rate of 1°C / min-2°C / min and maintain the temperature for 2h-3h.

[0042] Specifically, the crystal structures of manganese oxides formed under different calcination conditions are different. When the temperature is increased from room temperature to 750°C-850°C at a heating rate of 1°C / min-2°C / min and then kept constant for 2h-3h, oxygen-stable MnO can be generated. After using the surfactant CTAB, the (111) specific crystal plane can be fully exposed.

[0043] According to a third aspect of an embodiment of the present invention, there is provided an application of a cathode material that spontaneously forms a spinel-type lithium-rich metal oxide, wherein the transition metal oxide MO that exposes a specific crystal face is used as a positive electrode material in a lithium-oxygen battery.

[0044] Furthermore, the transition metal oxide MO with exposed specific crystal planes and the conductive carbon material are dissolved in a polyvinylidene fluoride N-methylpyrrolidone solution with a mass percentage concentration of 2%-7%, ultrasonicated for 30min-40min, and the obtained slurry is drop-coated on the carbon support to obtain the positive electrode material of the lithium oxygen battery.

[0045] The present invention uses transition metal oxide MO with exposed specific crystal faces as the positive electrode material, focusing on solving the problem of excessively high potential during charging due to the generation of Li2O2. Taking MnO(111) as an example, during the discharge process, when MnO is used as the positive electrode of a lithium-oxygen battery, the intermediate LiO2 - It is easy to contact with the (111) crystal plane of MnO and react to form lithium-rich manganese oxide (LiMnO4) instead of Li2O2, which can significantly reduce the required applied voltage (3.2V) during charging and greatly improve the energy efficiency of the battery (82.18%). During charging, the intermediate product LiMnO4 will decompose to produce single lithium (Li) and manganese oxide (MnO x ), which will not cause serious polarization due to oxygen oxidation problems in subsequent cycles. The cyclic charge-discharge test results show that at a current density of 500mA / g and a limited specific capacity of 500mAh / g, the use of MnO(111) can stabilize its reversible cycle at 56 times, and the first charging potential is only 0.2V higher than the 56th charging potential.

[0046] In some feasible embodiments, the conductive carbon material includes carbon fiber, carbon nanotube, graphite or conductive carbon black Super P. Preferably, the conductive carbon material is conductive carbon black Super P.

[0047] Specifically, carbon fiber: good but unstable electrical conductivity, high thermal stability, low density and specific surface area, good processing performance, lower processing difficulty than graphite, requires a specific production process, and its source is mainly organic fibers (such as PAN, asphalt or viscose fibers) carbonized at high temperature. Although it has excellent performance, it is cost-effective. Carbon nanotubes: excellent electrical conductivity, high conductivity and double layer effect, high thermal stability, high density and large specific surface area, general processing performance and difficult to disperse, require a specific production process, its source is mainly prepared by CVD and arc discharge, etc., cost-effective and greatly affected by output and preparation cost. Graphite: moderate and unstable electrical conductivity, moderate thermal stability, low density and specific surface area but large aspect ratio, general processing performance and requires special treatment to improve dispersion, high sustainability and abundant natural resources, its source is mainly natural minerals or artificial, formed by carbon elements under high temperature and high pressure, low cost-effectiveness and abundant sources. Super P (conductive carbon black): excellent conductive properties, high structure, high purity and high conductivity, high thermal stability, high density and specific surface area, good processing performance and easy dispersion and processing, good sustainability and a wide range of production raw materials. Its source is mainly obtained by incomplete combustion or thermal decomposition of organic matter (natural gas, heavy oil, etc.). Although the cost-effectiveness is relatively high, the performance is excellent. Compared with carbon fiber, carbon nanotubes and graphite, Super P (conductive carbon black) has excellent conductivity and does not fluctuate with temperature changes. In addition, its cheap, easy to obtain and easy to disperse properties also prove that it is a good choice as an excellent conductive auxiliary material. Taking all factors into consideration, the preferred conductive carbon material of the present invention is conductive carbon black Super P.

[0048] Example 1 A cathode material MnO that spontaneously forms a spinel-type lithium-rich manganese oxide 1. Method selection 1. Sol-gel method, the preparation method is as follows: 1) In a container, dissolve 2.45 g Mn(Ac)2, 6.25 g PVP, and 1 g CTAB in 50 mL DMF. Seal the container with a transparent film and place it on an electronic stirrer. Stir at room temperature for 12 h to form a uniform solution.

[0049] 2) The obtained uniform solution was transferred to a porcelain boat, placed in an oven at 60°C for 12 h, and then placed in a tubular atmosphere furnace filled with N2, and heated from room temperature to 800°C at a heating rate of 1°C / min. After maintaining the temperature for 2 h, it was naturally cooled to room temperature to obtain MnO.

[0050] 2. Electrospinning method, the preparation method is as follows: 1) In a container, 2.45 g Mn(Ac)2, 6.25 g PVP, and 1 g CTAB were dissolved in 50 mL DMF. The container was sealed with a transparent film and then placed on an electronic stirrer. After stirring at room temperature for 12 h, a uniform solution was formed to obtain an electrospinning precursor solution.

[0051] 2) The obtained electrospinning precursor solution was transferred to a 20 mL syringe for electrospinning to obtain electrospinning fibers. The electrospinning parameters were set as follows: voltage: 20 kV, injection rate: 0.5 mL / h, receiving distance: 12 cm.

[0052] 3) The obtained electrospun fiber was placed in a vacuum drying oven and dried at 60°C for 12 h. It was then placed in a tubular atmosphere furnace filled with N2 and heated from room temperature to 800°C at a heating rate of 1°C / min. After maintaining the temperature for 2 h, it was naturally cooled to room temperature to obtain MnO.

[0053] 3. Characterization Figure 1 The SEM images of MnO prepared by sol-gel method (A) and electrospinning method (B) are shown in Figure 2. Figure 1 As shown in Figure A, the MnO prepared by the sol-gel method is a nanoflower formed by tightly aggregated particles. This is because the sol-gel method is a preparation method in which a liquid sol loses its fluidity through heating or other heat treatment methods and gradually forms a rigid gel. In this process, the addition of CTAB will strengthen the metal ions (Mn 2+ ) interact with each other, and finally form aggregated nanoflowers. Figure 1 As shown in Figure B, the MnO prepared by electrospinning is uniformly dispersed and regularly shaped nanoparticles. This is because during the electrospinning process, the applied external voltage can enhance the stretching effect on the particles and fibers through electrostatic force, which helps to ensure the dispersion of metal ions, thereby forming uniformly dispersed and regularly shaped nanoparticles during subsequent heat treatment or carbonization.

[0054] Figure 2 The TEM image (A) and the corresponding HRTEM image (with SAED image embedded) (B) of a single MnO(111) nanocube prepared by electrospinning. Figure 2It can be seen that compared with the interplanar spacing of the standard MnO (111) crystal plane (d = 0.256nm), the MnO prepared by the electrospinning method of the present invention has d = 0.264nm, which is acceptable because there is a measurement error in the measurement. At the same time, the SAED graph also has only one set of symmetrical diffraction spots. Combined with the results of the interplanar spacing, it is proved that the MnO prepared by the electrospinning method provided by the present invention, the (111) crystal plane is fully exposed, which is attributed to the electrospinning method on the one hand and the use of CTAB on the other hand. As a cationic surfactant, it has a long hydrophobic chain and a positively charged quaternary ammonium salt head, so that it can be selectively adsorbed on the (111) crystal plane of MnO, and through the steric hindrance effect and electrostatic interaction, the growth rate of certain crystal planes is inhibited, so that it grows in a specific direction, forming a special structure and exposing the (111) specific crystal plane of MnO (111).

[0055] 2. Screening of manganese salts Here’s how: 1) In a container, dissolve 2.45g Mn(Ac)2 or 2.14g MnSO4 or 2.53g Mn(NO3)2, 6.25g PVP, and 1g CTAB in 50mL DMF, seal the container with a transparent film, and then place it on an electronic stirrer. Stir at room temperature for 12h to form a uniform solution to obtain an electrospinning precursor solution.

[0056] 2) The obtained electrospinning precursor solution was transferred to a 20 mL syringe for electrospinning to obtain electrospinning fibers. The electrospinning parameters were set as follows: voltage: 20 kV, injection rate: 0.5 mL / h, receiving distance: 12 cm.

[0057] The results show that Mn(Ac)2, MnSO4 or Mn(NO3)2 can successfully prepare electrospun fibers. It proves that different manganese salts do not affect the morphology of electrospun fibers, because PVP only reacts with Mn during the entire spinning process. 2+ Formation of Mn 2 + -PVP complex, anions do not affect its basic structure.

[0058] 3. Screening of surfactants Here’s how: 1) In a container, 2.45 g Mn(Ac)2, 6.25 g PVP, 1 g CTAB or 1 g sodium dodecyl sulfate or 1 g Tween 20 were dissolved in 50 mL DMF, the container was sealed with a transparent film, and then placed on an electronic stirrer. After stirring at room temperature for 12 h, a uniform solution was formed to obtain electrospinning precursor solutions of different surfactants.

[0059] 2) The electrospinning precursor solutions of different surfactants were transferred into a 20 mL syringe for electrospinning to obtain electrospinning fibers. The electrospinning parameters were set as follows: voltage: 20 kV, injection rate: 0.5 mL / h, receiving distance: 12 cm.

[0060] Figure 3 The following is a SEM image of electrospun fibers prepared with different surfactants. Different types of surfactants were added to the same spinning solution system, and the corresponding fiber materials were obtained after electrospinning. Figure 3 As can be seen in Figure A, when anionic surfactant, sodium dodecyl sulfate, is used, the corresponding fibers are not only entangled with each other, but also have poor continuity. Figure 3 As can be seen in Figure C, when the non-ionic surfactant Tween 20 is used, no obvious fiber structure is present in the fiber. Figure 3 It can be seen from Figure B that when a cationic surfactant, cetyl trimethyl ammonium bromide, is used, the corresponding fiber structure not only has a uniform size distribution, but also has no obvious agglomeration phenomenon between the fibers. Therefore, in the present invention, preferably, the surfactant is a cationic surfactant, more preferably, cetyl trimethyl ammonium bromide.

[0061] 4. Screening of surfactant concentration Here’s how: 1) In a container, add 2.45g Mn(Ac)2 and 6.25g PVP, then add 0g, 0.5g, 1g or 1.5g CTAB respectively, dissolve in 50mL DMF, seal the container with a transparent film, and then place it on an electronic stirrer. Stir at room temperature for 12h to form a uniform solution to obtain an electrospinning precursor solution.

[0062] 2) The obtained electrospinning precursor solution was transferred to a 20 mL syringe for electrospinning to obtain electrospinning fibers. The electrospinning parameters were set as follows: voltage: 20 kV, injection rate: 0.5 mL / h, receiving distance: 12 cm.

[0063] 3) The obtained electrospun fiber was placed in a vacuum drying oven and dried at 60°C for 12 h. It was then placed in a tubular atmosphere furnace filled with N2 and heated from room temperature to 800°C at a heating rate of 1°C / min. After maintaining the temperature for 2 h, it was naturally cooled to room temperature to obtain MnO.

[0064] Figure 4The corresponding SEM images of the products before and after calcination with different concentrations of CTAB are shown. The SEM images showing the effect of different amounts of CTAB added on the morphology of electrospun fibers and carbonized particles are shown. When CTAB is not added, the surface tension of the spinning solution is large, which makes it impossible to form fibers, which causes the heat-treated MnO nanoparticles to agglomerate together. When 0.5g CTAB is added, the surface tension of the spinning solution can be slightly reduced, but insufficient CTAB will cause the heat-treated MnO particles to grow amorphously, resulting in uneven size. When 1g CTAB is added, not only the electrospun fibers are evenly distributed, but also the heat-treated nanoparticles are evenly distributed, and the shapes and sizes are basically similar. When 1.5g CTAB is added, not only the fibers are overstretched to form fibers of uneven size, but almost no MnO is generated after calcination, because the excessive CTAB inhibits the growth of MnO seeds.

[0065] Figure 5 The following are the XRD patterns of the products after calcination with different concentrations of CTAB. The results show that when 0.5g CTAB is added, the crystallinity of MnO particles decreases, while the addition of 1g CTAB increases the crystallinity of MnO. The addition of 1.5g CTAB completely inhibits the growth of MnO crystals, and more crystalline carbon is formed. Therefore, the present invention preferably adds 2.45g Mn(Ac)2 to 1g CTAB (the addition amount of CTAB is 77.89% of the mass of the manganese element).

[0066] Example 2 Manganese oxide MnO with exposed (111) specific crystal face is used as positive electrode material in lithium oxygen battery Here’s how: 1. Preparation of manganese oxide MnO with exposed (111) specific crystal face 1) In a container, 2.45 g Mn(Ac)2, 6.25 g PVP, and 1 g CTAB were dissolved in 50 mL DMF. The container was sealed with a transparent film and then placed on an electronic stirrer. After stirring at room temperature for 12 h, a uniform solution was formed to obtain an electrospinning precursor solution.

[0067] 2) The obtained electrospinning precursor solution was transferred to a 20 mL syringe for electrospinning to obtain electrospinning fibers. The electrospinning parameters were set as follows: voltage: 20 kV, injection rate: 0.5 mL / h, receiving distance: 12 cm.

[0068] 3) The obtained electrospun fibers were placed in a vacuum drying oven and dried at 60 °C for 12 h. Then, they were placed in a tubular atmosphere furnace filled with N2 and heated from room temperature to 800 °C at a heating rate of 1 °C / min. After being kept at this temperature for 2 h, they were naturally cooled to room temperature to obtain MnO nanocubes with exposed (111) specific crystal faces, which were labeled as MnO (111).

[0069] 2. Preparation of positive electrode materials in lithium-oxygen batteries Weigh 5 mg MnO (111) and 1 mg Super P (conductive carbon black) and dissolve them in a 5% PVDF / NMP solution. Place them in an ultrasonicator for 30 minutes and then drop them onto a 2 cm diameter disc of carbon paper. The mass difference of the carbon paper before and after drop coating is calculated to obtain the mass of the loaded catalyst (the loading amount of the catalyst is: 0.5 mg~1 mg), and the positive electrode material is obtained.

[0070] 3. Assembly of lithium oxygen battery The structure of lithium oxygen battery mainly includes negative electrode shell, lithium sheet, electrolyte, diaphragm, positive electrode material and positive electrode shell. Lithium oxygen battery was assembled in a glove box (H2O<0.1ppm, O2<0.1ppm), in which the diaphragm used glass fiber diaphragm (Whatman) and the electrolyte used 1M LiTFSI / TETRGDME.

[0071] 4. Electrochemical test The method is based on the prior art.

[0072] Comparative Example: MnO (111) is not added to the positive electrode material.

[0073] 4.1) Charge and discharge test Figure 6 The deep discharge curves of the positive electrode materials Super P (A, C) or MnO (111) + Super P (B, D) at different current densities and the SEM images after discharge at 500mA / g. Figure 6 The results in Figures A and C show that as the current density increases, when the positive electrode material is only Super P, its deep discharge specific capacity decreases significantly. This is because the discharge product Li2O2 tends to form a needle-like or granular structure at high current density, which is also proven by the SEM image at 500 mA / g. Figure 6 The results in Figures B and D show that as the current density increases, the specific capacity of deep discharge does not decrease significantly when the positive electrode material is a combination of MnO(111) and Super P. This is because MnO(111) can interact with the intermediate LiO2 to generate a flake-structured LiMnO4 instead of Li2O2, which is also proven by the SEM image at 500 mA / g.

[0074] pass Figure 6 Comparison between A and B proves that MnO(111) prepared by the method of the present invention effectively prevents the formation of Li2O2.

[0075] 4.2) Charge and discharge cycle curve Figure 7 This is the charge and discharge cycle curve of MnO (111) after it is applied to lithium oxygen batteries. The cyclic charge and discharge test was carried out under the conditions of 500mA / g and 500mAh / g. Figure 7 The results show that the potential platform is 2.63V during the first discharge, and 3.2V during the first charge. At this time, the battery's energy efficiency is as high as 82.18%. At the same time, the ultra-low charging potential also means that there will be no other side reactions (such as carbon decomposition, electrolyte volatilization, etc.) at this time. After 56 cycles, the charging platform did not undergo obvious polarization. Compared with the first charging potential, the potential at this time only increased by 0.2V, and the energy efficiency at this time was only reduced by 4.83%. After continuing to cycle, the results showed that the battery cycle stopped at the 226th time.

[0076] 4.3) Figure 8 is the XRD pattern of the positive electrode after a specific number of discharge cycles. Figure 8 It can be seen that after the first discharge, in addition to the characteristic peaks of Li2O2 and LiOH, a weak characteristic peak also appeared at 23.45°, which corresponds to LiMnO4 (111). After the 56th cycle, the characteristic peak at 23.45° is more obvious. This is because after each charge, part of LiMnO4 will decompose to produce catalytically active MnO x The decomposition of Li2O2 is promoted, so that the charging potential is maintained at a stable platform. When the cycle continues, the presence of Li2O2 decomposition products will cause a certain degree of polarization of the potential, resulting in a sharp polarization of the potential in the subsequent cycle. The XRD after the 226th discharge proves that there is a characteristic peak at 18°, corresponding to Li 1.147 Mn 2.259 O4, and no other products, indicating that in the subsequent cycle process, due to the high charging potential, Li2O2 can be completely decomposed. But at the same time, LiMnO4 will be transformed into substances with different lithium-manganese atomic ratios due to the large fluctuation of potential: Li 1.147 Mn 2.259 O4.

[0077] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.

Claims

1. A cathode material that spontaneously forms a spinel-type lithium-rich metal oxide, characterized in that: The cathode material for spontaneously forming spinel-type lithium-rich metal oxide is a transition metal oxide MO with exposed specific crystal planes prepared by an electrostatic spinning method; wherein M=Mn, Co, Ni or Fe.

2. The cathode material of the spontaneously formed spinel lithium-rich metal oxide according to claim 1, characterized in that: The cathode material of the spontaneously formed spinel lithium-rich metal oxide is manganese oxide MnO which exposes a (111) specific crystal plane and is prepared by an electrospinning method.

3. A method for preparing a cathode material that spontaneously forms a spinel-type lithium-rich metal oxide, characterized in that: The method for preparing the cathode material of the spontaneously formed spinel lithium-rich metal oxide according to claim 1 or 2 comprises: Weighing manganese salt, cobalt salt, nickel salt or iron salt, polyvinyl pyrrolidone and cationic surfactant into a container, adding dimethylformamide to dissolve, sealing the container, stirring at room temperature for 10h-15h, and obtaining an electrospinning precursor solution; The electrospinning precursor solution is transferred into a syringe to prepare electrospinning fibers by an electrospinning method; The electrospun fiber is placed in a drying oven, dried at 50°C-70°C for 10h-15h, then heat treated in a N2 atmosphere, and then naturally cooled to room temperature to obtain a transition metal oxide MO with a specific crystal face exposed.

4. The preparation method according to claim 3, characterized in that: The manganese salt is selected from Mn(Ac)2, MnSO4 or Mn(NO3)2.

5. The preparation method according to claim 4, characterized in that: The cationic surfactant is hexadecyltrimethylammonium bromide; the added amount of the hexadecyltrimethylammonium bromide is 75%-85% of the mass of the manganese element.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The conditions of the electrospinning method are: voltage 20 kV-30 kV, injection rate 0.5 mL / h-1.0 mL / h, and receiving distance 12 cm-15 cm.

7. The preparation method according to any one of claims 3 to 5, characterized in that: The heat treatment is to increase the temperature to 750°C-850°C at a heating rate of 1°C / min-2°C / min and keep the temperature constant for 2h-3h.

8. An application of a cathode material that spontaneously forms a spinel-type lithium-rich metal oxide, characterized in that: The transition metal oxide MO with exposed specific crystal planes as claimed in claim 1 or 2 is used as a positive electrode material in a lithium oxygen battery.

9. The use according to claim 8, characterized in that: The transition metal oxide MO with exposed specific crystal planes and the conductive carbon material are dissolved in a polyvinylidene fluoride N-methylpyrrolidone solution with a mass percentage concentration of 2%-7%, ultrasonicated for 30min-40min, and the obtained slurry is drop-coated on a carbon carrier to obtain a positive electrode material for a lithium oxygen battery.

10. The use according to claim 9, characterized in that: The conductive carbon material includes carbon fiber, carbon nanotube, graphite or conductive carbon black Super P.

Citation Information

Patent Citations

  • Carbon confined metal or metal oxide composite nanostructure material and preparation method and application thereof

    CN107946560A

  • Monocrystal lithium-rich material, preparation method thereof and energy storage device

    CN116856058A

  • Cathode catalyst for lithium-air battery, method for producing same, and lithium-air battery comprising same

    KR1020140065515A

  • Graphene / mno electrode, preparation method therefor, and high energy density supercapacitor

    WO2022228137A1

Cited By

  • Preparation method of lithium nickel manganese oxide

    CN120681797A